2013
DOI: 10.1128/aac.02569-12
|View full text |Cite
|
Sign up to set email alerts
|

In VitroandIn VivoActivities of Dicationic Diguanidino Compounds against Echinococcus multilocularis Metacestodes

Abstract: c Alveolar echinococcosis (AE) is a disease predominantly affecting the liver, with metacestodes (larvae) of the tapeworm Echinococcus multilocularis proliferating and exhibiting tumor-like infiltrative growth. For many years, chemotherapeutical treatment against alveolar echinococcosis has relied on the benzimidazoles albendazole and mebendazole, which require long treatment durations and exhibit parasitostatic rather than parasiticidal efficacy. Although benzimidazoles have been and still are beneficial for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 36 publications
(34 reference statements)
2
15
0
Order By: Relevance
“…The complete results of this screening are shown in Table S1 . Seven of these drugs exhibited more than 50% of the activity of DB1127, one of the current lead compounds [15] , [16] and this was also confirmed by macroscopical observations of the vesicles. The 7 active compounds were further evaluated in a concentration series (20, 10, 5, 1, 0.1 µM) ( Figure 1 ).…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…The complete results of this screening are shown in Table S1 . Seven of these drugs exhibited more than 50% of the activity of DB1127, one of the current lead compounds [15] , [16] and this was also confirmed by macroscopical observations of the vesicles. The 7 active compounds were further evaluated in a concentration series (20, 10, 5, 1, 0.1 µM) ( Figure 1 ).…”
Section: Resultssupporting
confidence: 57%
“…Negative controls contained the corresponding amounts of DMSO. As a positive control DB1127 (20 µM) [15] , [16] was applied. PGI measurements were performed as described earlier [10] , with the difference that a 2300 EnSpire multilabel reader (Perkin-Elmer, Turku, Finland) was used for measurement of increase in absorbance at 340 nm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides benzimidazoles, these include dicationic diguanidino compounds (Küster et al, 2013); the antimalarials dihydroartemisinin and artesunate (Spicher et al, 2008a) and mefloquine (Küster et al, 2011); the cytostatic drugs vincristine, navelbine and methotrexate (Hübner et al, 2010); 2-methoxyestradiol a compound with documented anti-tumor activity (Spicher et al, 2008b), among others. However, none of the compounds investigated has been translated into clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo studies in the mouse model demonstrated the efficacy of oral application of the anti-malarial compound mefloquin, which will be followed up by studies on a range of mefloquine-derivatives that are predicted to have a lower capactiy to cross the bloodbrain barrier. Promising in vivo effects were also obtained with a pentamidine derivative, DB1127, however, only when the drug was applied intraperitoneally (Küster et al, 2013b). In addition, investigations on potential targets of selected drugs in Echinococcus are being carried out in order to explore their potential mechanism of action in the metacestode stage.…”
Section: B New Drug Targetsmentioning
confidence: 99%